Student perspective: AI in transforming IT engineering education - Useda Medrano, Joyce Francela (2025)
In the realm of higher education, particularly in fields related to technology and computer science, the integration of advanced tools such as artificial intelligence (AI) is gaining prominence. This research project focuses on analyzing students’ perceptions regarding the use of AI in solving programming problems in the Programming I and II courses of the Information Technology Engineering (ITI) program at the Guanacaste campus. The study applies a programming exercise both manually and with AI to compare resolution methods, identify difficulties, and assess students’ perceived knowledge. It seeks to determine the positive and negative factors of using AI in programming problem-solving. This project not only contributes to academic understanding of AI usage in education but also provides valuable insights for enhancing teaching methods in programming, preparing engineers for the technological challenges of the modern world. The results show a neutral attitude among students toward the impact of AI on their knowledge development, highlighting technical challenges and errors in problemsolving. Despite this, they recognize AI’s potential to enhance learning, suggesting the need for greater information and training on these technologies in the academic sphere.